Management of Neck Pain in Royal Australian Air Force Fast Jet Aircrew - Netto, Kevin; Hampson, G.; Oppermann, B.; Carstairs, G.; Aisbett, B. (Association of Military Surgeons of the U S, 2011)
To examine the type and effectiveness of various strategies used by Royal Australian Air Force (RAAF) fast jet (FJ) aircrew in self-referral and management of flight-related neck pain, a 6-section, 18-question survey tool was distributed to 86 eligible RAAF aircrew. Selective results from the sections evaluating aircrew demographics, incidence of flight-related neck pain, and the self-referral strategies of aircrew to manage these injuries are presented here. Eighty-two RAAF FJ aircrew responded to the survey. Ninety-five percent of the respondents experienced flight-related neck pain. The most commonly sought treatment modalities were on-base medical and physiotherapy services. Many respondents reported that currently provided on-base treatment and ancillary services such as chiropractic therapy are the most effective in alleviating symptoms. Further investigation into the effectiveness and safety of these ancillary therapies needs to be performed to allow appropriate consideration of their place in the management of neck pain in FJ aircrew.